2017
DOI: 10.1044/2016_jslhr-h-16-0237
|View full text |Cite|
|
Sign up to set email alerts
|

Normative Study of Wideband Acoustic Immittance Measures in Newborn Infants

Abstract: Objective The purpose of this study was to describe normative aspects of wideband acoustic immittance (WAI) measures obtained from healthy White neonates. Method In this cross-sectional study, wideband absorbance (WBA), admittance magnitude, and admittance phase were measured under ambient pressure condition in 326 ears from 203 neonates ( M age = 45.9 hr) who passed a battery of tests, including automated audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…In general, absorbance was highest between 1 and 2.5 kHz and lowest between 0.25 and 8 kHz. These results concur with the results reported by Wali et al (2017) and Aithal et al (2017) for both pressurised WBA conditions in neonates. Several studies have reported the frequency region between 0.8 and 2 kHz as being the most sensitive region to identify reduced middle-ear transmission and particularly relevant for middle ear assessments [4,5,9,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, absorbance was highest between 1 and 2.5 kHz and lowest between 0.25 and 8 kHz. These results concur with the results reported by Wali et al (2017) and Aithal et al (2017) for both pressurised WBA conditions in neonates. Several studies have reported the frequency region between 0.8 and 2 kHz as being the most sensitive region to identify reduced middle-ear transmission and particularly relevant for middle ear assessments [4,5,9,14].…”
Section: Discussionsupporting
confidence: 93%
“…Further, the pattern of WBA TPP in the Hunter et al study was different to that observed in the present study. Mean WBA TPP pattern in the present study exhibited a multipeaked pattern with two maxima around 1.25-1.5 kHz and 6 kHz which is similar to the WBA TPP pattern in earlier studies on neonates [15,16]. In…”
Section: Discussionsupporting
confidence: 90%
“…Test-retest reliability of WBT has been established, 1,2 and normative values are being developed for diverse pediatric patient populations. 2-6 When compared with traditional single-frequency tympanometry, WBT provides more information and demonstrates improved diagnostic potential for otitis media, middle ear effusion (MEE), and other pediatric conductive hearing–related pathologies, particularly at low-frequency ranges. 7-13…”
mentioning
confidence: 99%
“…In our study, when calculating A, the Titan system used the area of the calibration tube as the Most clinical WAI research has been focused on A and R since these measures are theoretically insensitive to probe location in the ear canal. There is interest, however, in using Y as well as A in diagnostic applications both for objectively interpreted predictive models Myers et al, 2018a;Piskorski et al, 1999;Sanford et al, 2009), and subjectively interpreted visual displays of results (Aithal et al, 2017;Allen et al, 2005;Sanford & Brockett, 2014;Sanford & Feeney, 2008;Voss et al, 2016). Knowledge of developmental effects on Y are essential for both of these applications.…”
Section: Clinical Significancementioning
confidence: 99%
“…Knowledge of the effect of maturation is important for these measures also, as there is interest in using Y and Z, as well as A and R, for the diagnosis of middle ear pathology in infants (Aithal et al, 2017;Ellison et al, 2012;Keefe et al, 2003a;Myers et al, 2018a;Sanford et al, 2009;Voss, Herrmann, Horton, Amadei, & Kujawa, 2016). Keefe et al (1993) studied changes in Z in a sample of infants aged 1 to 24 months (n = 15 at 1 month, 18 at 3 months; 11 at 6 months; 23 at 12 months; and 11 at 24 months).…”
Section: Introductionmentioning
confidence: 99%